SSPOL Member Publishes Research in New Book - Štefčík, Jozef, 1976-
Recenzia na odbornú monografiu týkajúcu sa tlmočníctva Theoretisch-pragmatische Reflexionen zur interlingualen Übersetzung ausgewählter Textsorten des Strafprozessrechts (Theoretical and Pragmatic Reflections on the Interlingual Translation of Selected Text Types of Criminal Procedure Law).